2019
DOI: 10.1093/infdis/jiz560
|View full text |Cite
|
Sign up to set email alerts
|

Varicella-Zoster Virus Infection of Primary Human Spinal Astrocytes Produces Intracellular Amylin, Amyloid-β, and an Amyloidogenic Extracellular Environment

Abstract: Background Herpes zoster is linked to amyloid-associated diseases, including dementia, macular degeneration, and diabetes mellitus, in epidemiological studies. Thus, we examined whether varicella-zoster virus (VZV)-infected cells produce amyloid. Methods Production of intracellular amyloidogenic proteins (amylin, amyloid precursor protein [APP], and amyloid-β [Aβ]) and amyloid, as well as extracellular amylin, Aβ, and amyloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…The pathogenesis of Alzheimer's disease is complex and involves multiple genetic and environmental factors, and our purpose is to present a new hypothesis that links mitochondrial dysfunction, cerebral energetics, cerebral insulin resistance, and diet that might encourage further research. We do not negate the role of other factors, such as varicella-zoster viral infection, that may induce similar pathways (Bubak et al, 2019). We also recognize that the role of dietary fats is complex and that the balance of omega3 to omega6 may also be important, and how this relates to fructose metabolism requires further study (Simopoulos, 2013).…”
Section: Limitationsmentioning
confidence: 86%
“…The pathogenesis of Alzheimer's disease is complex and involves multiple genetic and environmental factors, and our purpose is to present a new hypothesis that links mitochondrial dysfunction, cerebral energetics, cerebral insulin resistance, and diet that might encourage further research. We do not negate the role of other factors, such as varicella-zoster viral infection, that may induce similar pathways (Bubak et al, 2019). We also recognize that the role of dietary fats is complex and that the balance of omega3 to omega6 may also be important, and how this relates to fructose metabolism requires further study (Simopoulos, 2013).…”
Section: Limitationsmentioning
confidence: 86%
“…27,28 In a spinal astrocyte cell culture study, VZV-infected cells led to intracellular amyloid accumulation, but whether dementia occurs due to amyloid accumulation induced by HZI remains unclear. 29 Vascular dementia accounts for up to 20% of all cases of dementia and is caused by multiple cerebral infarctions from cerebrovascular or cardiovascular problems, including DM, hypertension, stroke and metabolic syndrome. 30 VZV invades the spinal cord or cerebral arteries directly or after reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…it was shown that the peptide inhibits the replication of seasonal and pandemic strains of H3N2 and H1N1 influenza A virus (IAV) in vitro 56 . Moreover, VZV-infection of primary human spinal astrocytes induce an extracellular amyloidogenic environment 57 . Clinical studies reveal a deposition of amyloid-ß plaques in the brains of HIV-infected individuals 58 and infections by HSV cause not only elevated ß-amyloid production but also phosphorylation of Tau 59,60 .…”
Section: Discussionmentioning
confidence: 99%